Aktivitas Antioksidan dan Inhibitor Alfa Glukosidase dari Fraksi Berbeda Rumput Laut Cokelat (Sargassum sp.) - Rahel Eriani Maria Manurung; Andarini Diharmi; Edison Edison (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
Sargassum sp. is one of the brown seaweed that contains bioactive compounds, which have antioxidant and alpha glucosidase inhibitor activity. This research aimed to determine the rendemen, secondary metabolic, total phenolic, antioxidant, and alpha glucosidase inhibitor from the extract and fractions of Sargassum sp. The research method used was an experiment by extracting Sargassum sp with methanol and the extract were fractionated with different polarity solvents (n-hexane, ethyl acetate, and ethanol). Data were analyzed descriptively. The analysis parameters consisted of rendemen, secondary metabolic (qualitative), total phenolics, antioxidants (DPPH and FRAP), and alpha glucosidase inhibitors. The results showed that the rendemen of the n-hexane, ethyl acetate, and ethanol fractions were 4,15, 5,81, and 4,94%, respectively. The secondary metabolic analysis of methanol extract were alkaloids, steroids/terpenoids, saponins, and phenolic. The n-hexane fraction were steroids/terpenoids, saponins, and phenolic. The ethyl acetate fraction were alkaloids, steroids/terpenoids, saponins, and phenolic. The ethanol and water fractions contained only saponins. The total phenolic content of the methanol extract, n-hexane, ethyl acetate, and etanol fractions were 21161,03, 7854,46, 1626,89, and 80,17 ppm. Antioxidants in methanol extract, n-hexane, ethyl acetate, ethanol fractions using DPPH were 329,42, 466,25, 535,08, and 80,17 ppm. Antioxidants in methanol extract, n-hexane, ethyl acetate, and ethanol fractions using FRAP were 196,15, 294,88, 364,26, and 492,68 ppm. Alpha glucosidase inhibitor in n-hexane fraction with an IC50 value of 538110,9 ppm. Extract and fractions of Sargassum sp. with different polarity solvents contained different secondary metabolic. Saponins were found in all solvents, phenolics and steroids/terpenoids were found in methanol extract, n-hexane, and ethyl acetate fractions, alkaloids were found in methanol exract and ethyl acetate fraction. The n-hexane fraction showed the highest activity in total phenol, antioxidant, and alpha glucosidase inhibitor.